2013
DOI: 10.1002/anie.201307475
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Hybrid Nanosheets of Tungsten Disulfide and Reduced Graphene Oxide as Catalysts for Enhanced Hydrogen Evolution

Abstract: Composite materials: Tungsten disulfide and WS2 /reduced graphene oxide (WS2 /rGO) nanosheets were fabricated by hydrothermal synthesis using tungsten chloride, thioacetamide, and graphene oxide (GO) as starting materials. The WS2 nanosheets are efficiently templated on the rGO layer. The WS2 /rGO hybrid nanosheets show much better electrocatalytic activity for the hydrogen evolution reaction than WS2 nanosheets alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
347
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(361 citation statements)
references
References 30 publications
14
347
0
Order By: Relevance
“…However, the above overpotential for HER in Figure 6 a is larger than that exhibited by the Ptfree electrodes such as MoS 2 and WS 2 -RGo composite electrodes, which have demonstrated an excellent HER activity in acidic medium. [62][63][64][65] Hence, we further investigated the catalytic activity of the NiS-Ti electrode towards HER in 0.5 M H 2 SO 4 solution, which demonstrated the evolution of hydrogen at a small overpotential of 0.12 V ( Figure 7 a). This activity is comparatively better than that demonstrated previously by the MoS 2 and WS 2 -RGo composite electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the above overpotential for HER in Figure 6 a is larger than that exhibited by the Ptfree electrodes such as MoS 2 and WS 2 -RGo composite electrodes, which have demonstrated an excellent HER activity in acidic medium. [62][63][64][65] Hence, we further investigated the catalytic activity of the NiS-Ti electrode towards HER in 0.5 M H 2 SO 4 solution, which demonstrated the evolution of hydrogen at a small overpotential of 0.12 V ( Figure 7 a). This activity is comparatively better than that demonstrated previously by the MoS 2 and WS 2 -RGo composite electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…A common strategy to improve the conductivity of MX 2 electrolysts is modification with conductive carbon or metal. [137,146,147] Recent studies on integration of carbon materials such as carbon nanotubes, [148,149] carbon boxes [150] and reduced graphene oxide [43] with interlayerexpanded MoS 2 for improving HER performance are extensively investigated. For instance, Lan and co-workers employed a one-step hydrothermal method to synthesize MoS 2 /N-doped rGO nanocomposite with interlayer spacing of 0.95 nm as HER electrocatalyst.…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
“…Since the discovery of graphene, 2D materials, such as tungsten disulfide (WS 2 ) and other transition metal dichalcogenides (TMDCs), have drawn a great deal of interest due to their attractive physical and electronic properties [1][2][3]. It is reported that the hydrogen binding energy of MoS 2 is close to that of Pt-group metals, thus hinting at potential applications of other TMDCs in photocatalytic HER [4][5][6][7][8][9]. Both computational and experimental results have confirmed that the photocatalytic activities of XS 2 (X could be other transition metals, such as W) mainly stem from the edges rather than the basal planes [10,11].…”
Section: Introductionmentioning
confidence: 99%